2020
DOI: 10.1063/5.0021564
|View full text |Cite|
|
Sign up to set email alerts
|

Application of genetic fuzzy immune PID algorithm in cruise control for commercial vehicles

Abstract: Cruise control when driving downhill is one of the most important functions of commercial vehicles equipped with an auxiliary brake system. A genetic fuzzy immune PID algorithm is proposed to achieve a constant speed in this study. An immune feedback algorithm is used to adjust the proportional coefficient, and the fuzzy algorithm is used to adjust the integral coefficient and the differential coefficient. At the same time, the genetic algorithm is used to optimize the immune parameters to overcome the problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The advantages of the proposed algorithm are verified by experiments in terms of solution accuracy and convergence speed. Jing proposed a genetic fuzzy immune PID algorithm to achieve a constant speed in this study [8]. The results showed that the algorithm has a significant effect.…”
Section: Introductionmentioning
confidence: 88%
“…The advantages of the proposed algorithm are verified by experiments in terms of solution accuracy and convergence speed. Jing proposed a genetic fuzzy immune PID algorithm to achieve a constant speed in this study [8]. The results showed that the algorithm has a significant effect.…”
Section: Introductionmentioning
confidence: 88%
“…However, the hybridization probability Pc and mutation probability Pm of the above genetic algorithms often adopt fixed values or fixed functions to adjust the parameters. However, it is very difficult to determine an appropriate Pc and Pm: when large values are used, good individuals may be destroyed, and the genetic algorithm turns arbitrary search algorithm, which destroys the stability and robustness of the algorithm, whereas when a smaller value is adopted, the algorithm will lose its ability to maintain population diversity, leading to premature convergence of the algorithm and falling into local solutions [5]. ey are frequently used in industry for a range of tasks such as issue prediction, fault diagnostics, centralized management, energy management, production management, and computer engineering, to mention a few [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…ere has been a surge of attention in the use of FNNs to handle variables only with the potential of creating a model to learn from operations in recent years [5].…”
Section: Introductionmentioning
confidence: 99%